2009
DOI: 10.1074/jbc.m109.032870
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Mechanism of Activation of the Epithelial Na+ Channel by Cleavage

Abstract: We examined activation of the human epithelial sodium channel (ENaC) by cleavage. We focused on cleavage of ␣ENaC using the serine protease subtilisin. Trimeric channels formed with ␣FM, a construct with point mutations in both furin cleavage sites (R178A/R204A), exhibited marked reduction in spontaneous cleavage and an ϳ10-fold decrease in amiloride-sensitive whole cell conductance as compared with ␣WT (2.2 versus 21.2 microsiemens ( S)). Both ␣WT and ␣FM were activated to similar levels by subtilisin cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 39 publications
1
31
0
2
Order By: Relevance
“…Multiple mechanisms are known to participate in the regulation of ENaC activity, including limited proteolysis (30,43,44), hormonal mediated effects on translocation and membrane assembly (9,13,45,46), a serum and glucocorticoid-regulated kinase (SGK-1)-mediated phosphorylation of Nedd4 -2 leading to reduced ubiquitination, retrieval and degradation (17,18,47,48), as well as negative and positive hormonal effects mediated by protein kinases including ERK1/2, protein kinases A and C, and phosphatidylinositol 3-kinase, among others (14 -19, 47-49). Added to the above is the present identification of the Cyp2c44 epoxygenase and its EET metabolites as a new class of in vivo regulators of ENaC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms are known to participate in the regulation of ENaC activity, including limited proteolysis (30,43,44), hormonal mediated effects on translocation and membrane assembly (9,13,45,46), a serum and glucocorticoid-regulated kinase (SGK-1)-mediated phosphorylation of Nedd4 -2 leading to reduced ubiquitination, retrieval and degradation (17,18,47,48), as well as negative and positive hormonal effects mediated by protein kinases including ERK1/2, protein kinases A and C, and phosphatidylinositol 3-kinase, among others (14 -19, 47-49). Added to the above is the present identification of the Cyp2c44 epoxygenase and its EET metabolites as a new class of in vivo regulators of ENaC activity.…”
Section: Discussionmentioning
confidence: 99%
“…4 To circumvent these problems, we developed this assay using peptides with sequences specific to ENaC. Assuming that these sites are solution-accessible in the channel, a finding verified experimentally by our laboratory and by other investigators (21,22,29), it is likely that the reported activity is a reasonable representation of the activity of proteases that can target these sites. This approach sacrifices the ability to identify a specific proteases, probably a complicated issue because many proteases may act on these ENaC sequences, especially given the number of proteases that have been shown to cleave the ENaC subunits (see discussion in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…This approach sacrifices the ability to identify a specific proteases, probably a complicated issue because many proteases may act on these ENaC sequences, especially given the number of proteases that have been shown to cleave the ENaC subunits (see discussion in Ref. 29). However, this approach results in a better understanding of the overall activity of proteases targeting these sequences and therefore provides a better representation or index of real-time channel activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism of how cleavage activates ENaC is incompletely understood, but one hypothesis is that cleavage removes inhibitory peptides from ␣ENaC and ␥ENaC (12). An alternative mechanism of ENaC activation by cleavage, proposed by Hu et al (14), involves loss of the ␣ENaC N terminus (including the first transmembrane domain) from the channel complex. Cleavage by proteases does not change the number of ENaC channels at the surface but rather increases channel open probability and is a mechanism for regulating ENaC activity (13).…”
mentioning
confidence: 99%